Children with word finding difficulties: Continuities and profiles of abilities. Issue 5 (October 2013) - Messer, David; Dockrell, Julie E.
Word finding difficulties (WFDs) occur in more than a quarter of children who are receiving speech and language therapy. This study provides the first investigation of the continuity in WFDs and investigates whether WFDs are associated with phonological or semantically related abilities. Thirty-eight children with WFDs were seen at age 7;0 and at 9;8. Standardized assessments of word finding, language and literacy were administered. The children's WFDs and other language abilities showed high levels of stability. Despite their WFDs, many children had standardized scores of phonological awareness, decoding and spelling in the typical range. In contrast, semantic fluency was particularly impaired, and WFDs were a significant predictor of reading comprehension. Cluster analysis indicated that there was one group of children with a profile similar to 'poor comprehenders' and a second with depressed language scores indicative of specific language impairment. The relevance of these findings to understanding the causes of WFDs is discussed.